Assessment of the Socio-Economic Status of Apartments in Kathmandu Valley - Shrestha, Archana Bade (Journal of Science and Engineering, 2019)
Nepal is urbanising at a rapid pace. According to CBS 2011 the urban population accounts for 17% and Kathmandu valley shares the highest urban population. The growing population has put immense pressure on land and housing situation in Kathmandu Valley. Apartments came into picture to accommodate the growing population in the less horizontal space of land but all income groups of people could not afford and access to the facilities and space provided in the apartments. The current scenario in Kathmandu valley depicts that the developers make investments in construction of apartments as a commercial activity rather than to upgrade housing scenario. Despite, due to the high interest rate, formal collateral in the form of land and house and high income of people to repay loans preferred by commercial banks, the economically weaker section and lower income group of people are not eligible to proceed for the loan. The high cost of Apartment units is beyond affordability of EWS and LIG. The rapid increment of population concentration on primate cities like Kathmandu has led to scarcity of land to accommodate the increasing migrants and not only that, it has resulted in the unhygienic condition of living, suffocating and deteriorating urban environment. As a result, the high income group are moving in the urban fringe and it’s always the poor who are trapped in the vulnerable core cities of Kathmandu. The residential shift of rich people to urban fringe has led to the adhoc development with social disparity and inequity amongst the people living in the same areas.